Transcriptomic and metabolic analysis unveils the mechanism behind leaf color development in Disanthus cercidifolius var. longipes - Tian, Xiaoming; Xiang, Guangfeng; Lv, Hao; Zhu, Lu; Peng, Jing; Li, Gaofei; Mou, Cun (Frontiers in Molecular Biosciences, 2024)
Introduction: Leaf coloration in Disanthus cercidifolius var. longipes results from the interplay of various pigments undergoing complex catalytic reactions. Methods: We aimed to elucidate the mechanisms of pigment biosynthesis affecting leaf color transition in D. cercidifolius var. longipes by analyzing variations in pigment accumulation and levels of gene expression. Results: We identified 468, 577, and 215 differential metabolites in green leaves (GL), gradual-color-changing leaves (GCCL), and red leaves (RL), respectively, with 94 metabolites shared across all comparisons. Metabolite accumulation patterns were similar among GL, GCCL, and RL, with flavonoids being the main differential metabolites. Delphinidin, malvidin, and petunidin derivatives were mostly accumulated in GCCL, whereas cyanidin, pelargonidin, and peonidin derivatives accumulated in RL. Transcriptome sequencing was used to identify differentially expressed genes. The expression of anthocyanin biosynthetic pathway genes was associated with anthocyanin accumulation patterns. Discussion: Our findings reveal that the content of delphinidin, malvidin, petunidin, and carotenoids collectively determines the gradual transition of leaf color from green in spring and summer to green, purple, and orange-yellow in early autumn, whereas the content of cyanidin, peonidin, pelargonidin, and carotenoids together causes the autumnal transition to red or orange-red colors as leaves of D. cercidifolius var. longipes age.